Social context, interaction and expectation play a role in alcohol use amongst Australian and Danish women aged 50 to 70 years. Issue 9 (30th October 2020) - Grønkjær, Mette; Dare, Julie; Kusk, Kathrine Hoffmann; Traumer, Line; Uridge, Lynsey; Wilkinson, Celia
Abstract: In this study, researchers explored the relationship between alcohol use and life transitions among women aged 50 to 70 years in Australia and Denmark. Data were collected via semi-structured interviews of 49 women, with thematic analysis indicating that alcohol use is a normal and accepted activity among Australian and Danish women. Alcohol use was influenced by women's specific life transitions including their retirement status. Using alcohol as a crutch was not a legitimate story, but women found it acceptable to temporarily manage stress. The researchers provided insight to women's perceptions on drinking that may guide future international public health strategies for this group.